Road Transportation and Energy Integration Strategy in China - Jia Limin; Ji Li (中国工程科学, 2022)
Transportation and energy are crucial for social development and civilization evolution. The energization of transportation infrastructure assets and clean transformation of transportation energies are effective decarbonization strategies for solving severe challenges such as resource shortage, climate change, and environmental pollution. This study first reviews the integration history of road transportation and energy, and investigates the demand for and trends of the integration from the perspectives of national energy security, clean transformation of energy supply, energization potential of transportation infrastructure assets, and intelligentization of the transportation system. The pathway for promoting the integrated development of road transportation and the energy sector is proposed based on assessing the wind and solar resources and the self-consistent supply capacity of energies within the road transportation system. Moreover, a roadmap for integrating road transportation and renewable energies is proposed considering the carbon peak and carbon neutralization targets. Finally, suggestions are proposed from two aspects. In terms of technology development, we suggest that China should enhance technology research and development, improve the industry chain, and promote technology innovation and integration. Additionally, it should provide policies for improving top-level design and strategic planning, exploiting new market modes, and strengthening international cooperation.